Cultivating green minds: a systematic review of teaching strategies, outcome and challenges in Education for Sustainable Development (ESD) for secondary schools - Mohd Loqmanul Hakim Kamaruldzaman; Kamisah Osman; Siti Nur Diyana Mahmud (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study conducts a systematic literature review to provide a comprehensive analysis of teaching strategies implemented in secondary schools for the integration of Education for Sustainable Development (ESD). Despite the global emphasis on ESD, a systematic comparison of teaching strategies' efficacy in secondary schools remains underexplored, particularly in diverse cultural contexts. The research explores prevalent teaching approaches, evaluates their outcomes, and identifies barriers and challenges encountered during implementation. To address this gap, the study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A meticulous analysis of 23 studies (2019–2024) from Scopus, Web of Science, and ERIC reveals that Project-based Learning (PjBL) dominates (48% of studies), significantly enhancing systems thinking and collaborative skills while Digital-based Learning (DBL) (30% of studies) proves most effective in technology-rich environments. Four key implementation challenges emerge, including the insufficient training of teachers, the lack of teaching materials, insufficient understanding of how to implement ESD and teachers' preference for subject-specific over cross-disciplinary approaches. These findings offer a research-backed foundation for selecting effective strategies, calling on policymakers to adopt flexible ESD frameworks tailored to local contexts while advancing SDG 4.7 objectives. Such efforts can narrow the longstanding divide between ESD principles and classroom implementation, enabling secondary schools globally to foster environmentally and socially conscious learners prepared for complex future demands.